Fundamental Aspects of Lipid-Based Excipients in Lipid-Based Product Development - Deepa Nakmode; Valamla Bhavana; Pradip Thakor; Jitender Madan; Pankaj Kumar Singh; Shashi Bala Singh; Jessica M. Rosenholm; Kuldeep K. Bansal; Neelesh Kumar Mehra (MDPI AG, 2022)
Poor aqueous solubility of drugs is still a foremost challenge in pharmaceutical product development. The use of lipids in designing formulations provides an opportunity to enhance the aqueous solubility and consequently bioavailability of drugs. Pre-dissolution of drugs in lipids, surfactants, or mixtures of lipid excipients and surfactants eliminate the dissolution/dissolving step, which is likely to be the rate-limiting factor for oral absorption of poorly water-soluble drugs. In this review, we exhaustively summarize the lipids excipients in relation to their classification, absorption mechanisms, and lipid-based product development. Methodologies utilized for the preparation of solid and semi-solid lipid formulations, applications, phase behaviour, and regulatory perspective of lipid excipients are discussed.